Immediate effects of cervical unilateral anterior-posterior mobilisation on shoulder pain and impairment in post-operative arthroscopy patients - Hauswirth, J.; Ernst, M.; Preusser, M.; Meichtry, A.; Kool, J.; Crawford, Rebecca (IOS Press, 2017)
Â© 2017 - IOS Press and the authors. All rights reserved. BACKGROUND: Lateral gliding cervical spine mobilisation is shown to improve shoulder pain, disability and function. However, despite common clinical-use, no study reports the effect of unilateral anterior-posterior (A-P) cervical mobilisation on shoulder pain and function, and particularly in patients after arthroscopic shoulder surgery. OBJECTIVE: Examine the immediate effect of single-level Grade III cervical unilateral A-P mobilisation on shoulder pain, flexion and abduction range of motion (ROM) and external rotator strength compared to placebo cervical unilateral A-P light touch pressure. METHODS: Single session intervention with a crossover design in 32 (15 women) postoperative arthroscopic shoulder patients. RESULTS: Immediate and superior treatment effects were shown for A-P cervical mobilisation in improving flexion ROM, isometric strength of external rotation, and pain intensity during flexion (all p< 0.05) when compared to the placebo. However, effects may not be considered clinically meaningful. CONCLUSION: Unilateral A-P mobilisation applied to the cervical spine shows a tendency toward positively influencing post-Arthroscopy shoulder pain and function. Further study examining cervical mobilisations directed in different planes to influence shoulder motion appear warranted.